NEGOSIASI LEMBAGA ADAT MELAYU RIAU KECAMATAN MANDAU DENGAN YAYASAN RAJA TAWAR MULA JADI DALAM PENYELESAIAN KONFLIK PERESMIAN BALAI ADAT BATAK DI KECAMATAN MANDAU - Umroh Isradana; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
In 2018, in Mandau District, Bengkalis Regency, there was a conflict regarding the inauguration of the Batak Traditional Hall. The rejection of the inauguration was carried out by the Lembaga Adat Melayu Riau (LAMR) Mandau due to the inauguration of the Balai Adat Batak in contradiction with the vision and mission of Riau 2020 which made Riau the center of Malay culture throughout Southeast Asia. Therefore, the event (LAMR) Mandau negotiated with the owner of rumah adat so that the inauguration of the balai adat was canceled. The purpose of this study was to determine the strategies of negotiating both parties, the stages in negotiating both parties, and the meaning of traditional houses for both parties.The research method used in this study is a qualitative descriptive method, by setting 8 (eight) research subjects as informants through a purposive technique. Data collection techniques used in this study were interviews and documentation. The data analysis technique in this study uses an interactive data model. Checking data uses the technique of extending participation and triangulation.The results of the study indicate that the negotiation strategy used by both parties is the Win-Lose strategy. This is because both parties both went to win in the negotiations, and the end result of the LAMR Mandau won by the cancellation of the inauguration of the Balai Adat Batak. In carrying out this strategy is assisted by negotiation techniques used by the LAMR Mandau was to make an agenda. Meanwhile the owner of traditional houses did not do any techniques. Mediation is another technique used by both parties to reach an agreement, because during the negotiations there was no meeting point. In interpreting traditional houses there is a slight difference in meaning. The owner of Balai Adat batak means as a form of symbols and inheritance that must be preserved wherever they are. However, both parties agreed that Balai Adat is the institutional center of a culture, which in the Balai Adat is that all traditional elders meet, conduct deliberations and cultural activities are carried out.Keyword: Negotiation, Conflict, Balai Adat